Effectiveness of the combination of biopellet, biochar, chicken manure and fish waste to the improvement of chemical properties of sandy soil and soybean plant growth - Sugeng Winarso; Bambang Hermiyanto; Sukron Romadhona; Marinus H Pandutama; Tri Candra Setiawati; I Indasah (Journal of Degraded and Mining Lands Management, 2020)
Most of the activities of the use of organic fertilizers and natural additions of organic matter in agricultural intensification fields in Indonesia have not been able to compensate for the rate of decline in soil organic matter by the decomposition process. Biochar has a high C level and has the mean residence time in a long period in the soils. It has been proven that biochar applications may increase soil Carbon but have not been able to increase plant production. Therefore, the use of biochar combined with organic waste rich in nutrients is essential to develop. The purpose of this study was to determine the effectiveness of some biochar compositions with sugar cane, chicken manure, fish waste in the form of biopellet fertilizer on improving the chemical properties of sandy soils and the vegetative growth of soybean plants. This study used a completely randomized block design with two factors. The first factor (B) was the composition of biochar consisting of three levels, namely: 70% biochar, 15% chicken manure, 15% fish waste (B1), 50 % biochar, 25% chicken manure, 25% fish waste (B2), and 20% biochar, 40% chicken manure, 40% fish waste (B3). The second factor (D) was the dose of biopellet fertilizers consisting of four levels, namely: control (D0), 2.5 t/ha (D1), 5 t/ha (D2), and 10 t/ha (D3). The results showed that the addition of biopellet fertilizer effectively improved soil chemical properties (pH, C-organic, and CEC) and the availability of N, P, and K of the sandy soil. The effectiveness of increasing the soil total-N varied from 32.42 to 75.79%, P-available varied from 17.46 to 40.69%, and exchangeable K ranged from 8.7 to 25.67%. Improvement of soil chemical properties and the availability of N, P, and K by biopellet fertilizer application increased plant growth but reduced the weight of root nodules.